Design of the Curtain Wall Cleaning Robot. Issue 1 (May 2019) - Fan, Shan; Han, Lei-lei; Meng, Chao-ying
Abstract: The curtain wall cleaning robot suitable for special-shaped wall structure of buildings is designed, and the mechanical structure design and control system design of the curtain wall cleaning robot is completed in the paper.The curtain wall cleaning robot is composed of two parts with the same structure. The hinge mechanism is used to realize the turning action of irregular wall. The suction and movement of the cleaning robot are realized by vacuum adsorption of the sucker. And the motor controlled the rotation of the roller brush. The screw guide rail drives the roller brush up and down to realize cleaning. Based on the mechanical structure design, the control system of curtain wall cleaning robot is designed. And PLC control system is used to control the sequence of action of curtain wall cleaning robot.